Resin composition and molded article

By integrating alicyclic structures into polycarbonate resin, the composition achieves improved transparency, heat resistance, and weather resistance, addressing the limitations of traditional resin blends.

JP7613908B2Active Publication Date: 2025-01-15TEIJIN LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2020212325
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-12-22
Publication Date
2025-01-15
Estimated Expiration
2040-12-22

AI Technical Summary

Technical Problem

Existing resin compositions of polycarbonate and acrylic resins suffer from issues such as poor weather resistance, low impact resistance, and incompatibility, leading to opaque materials and poor optical properties, with compositions containing aromatics exacerbating these problems.

Method used

Incorporating a specific alicyclic structure into the polycarbonate resin, specifically through the use of repeating units derived from alicyclic diols like 2,2,4,4-tetramethyl-1,3-cyclobutanediol, enhances transparency, heat resistance, and impact resistance, while maintaining compatibility with acrylic resin to achieve a transparent and durable composition.

Benefits of technology

The resulting resin composition exhibits excellent transparency, heat resistance, low photoelastic coefficient, and improved surface hardness, with enhanced weather resistance and moisture resistance, suitable for various applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007613908000001
    Figure 0007613908000001
  • Figure 0007613908000002
    Figure 0007613908000002
  • Figure 0007613908000003
    Figure 0007613908000003
Patent Text Reader

Abstract

To provide a resin composition which has excellent characteristics such as transparency, heat resistance, a low photoelastic coefficient, impact resistance, weather resistance, surface hardness and moist heat resistance, and contains a polycarbonate resin and an acrylic resin.SOLUTION: A resin composition contains a polycarbonate resin (A) containing 5 mol% or more and 90 mol% or less in the total repeating units (a) represented by the following formula (a), and an acrylic resin (B), in which a weight ratio of the polycarbonate resin and the acrylic resin is 1:99 to 99:1. In the formula, Cm represents an alkylene group having a cyclic structure, m represents an integer of 3-20, R represents an alkyl group having 1-20 carbon atoms or a cycloalkyl group having 3 to 10 carbon atoms, and n represents an integer of 1-10.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resin composition containing a polycarbonate resin and an acrylic resin, and a molded article thereof. [Background technology]

[0002] Conventionally, methacrylic resins, polycarbonate resins (hereinafter sometimes referred to as PC), etc. are known as transparent resins, and these resins are used in a wide range of fields such as electrical and electronic components, optical components, automotive components, and mechanical components in the form of molded products, films, sheets, etc.

[0003] Methacrylic acid resins such as polymethyl methacrylate (hereinafter sometimes referred to as PMMA) have high transparency and high surface hardness (pencil hardness H to 3H), and are widely used as optical materials such as lenses and optical fibers. However, their glass transition temperature is low at about 100°C, and their heat resistance is poor, limiting their use in fields requiring heat resistance. Another problem is that they have low impact resistance.

[0004] Polycarbonate resins made from bisphenol A are widely used in vehicle applications and building materials because of their excellent heat resistance, impact resistance, flame retardancy, and transparency. Among these applications, high weather resistance is required, especially for those used outdoors, but the weather resistance of polycarbonate resins is generally not as good as other transparent materials such as acrylic resins, and yellowing and devitrification occur when exposed to the outdoors. In addition, there is a problem that the surface is very soft (pencil hardness 4B to 2B) and easily scratched.

[0005] It is known that a mixture of PC and PMMA is essentially incompatible and produces an opaque material. For example, Patent Document 1 shows that a mixture of PC and PMMA is opaque and does not exhibit the physical properties of both polymers. In addition, Non-Patent Documents 1 and 2 report that a mixture of PC / PMMA is not miscible over the entire composition range and is opaque. On the other hand, Patent Document 2 shows that a composition of a polycarbonate resin containing a fluorinated monomer and an acrylic resin becomes transparent, but these compositions have problems in terms of optical properties such as weather resistance and photoelastic coefficient because the polycarbonate resin contains aromatics. In Patent Document 3, a transparent resin composition is obtained by modifying an acrylic resin, but since the acrylic resin contains aromatics, this composition also has problems in terms of optical properties such as weather resistance and photoelastic coefficient. In order to solve these problems, a resin composition with an acrylic resin using a polycarbonate having a special structure has been reported (Patent Document 4), and the excellent properties of PC and PMMA have been achieved. However, according to the study by the present inventors, it was found that the resin composition described in Patent Document 4 is significantly deteriorated in a moist and hot environment. Therefore, no composition of polycarbonate and acrylic resin that has good moist heat resistance while simultaneously achieving the properties of each resin has been reported so far. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] U.S. Pat. No. 4,319,003 [Patent Document 2] Japanese Patent Application Publication No. 07-3104 [Patent Document 3] JP 2014-1267 A [Patent Document 4] JP 2015-232091 A [Non-patent literature]

[0007] [Non-Patent Document 1] Polymer Preprints (Volume 23, pages 258-259, 1982) [Non-Patent Document 2] Advances in Chemistry(Volume 206, No.9, pages 129-148, 1984) Summary of the Invention [Problem to be solved by the invention]

[0008] An object of the present invention is to provide a resin composition containing a polycarbonate resin and an acrylic resin, which has excellent properties such as transparency, heat resistance, low photoelastic coefficient, impact resistance, weather resistance, surface hardness and moist heat resistance. [Means for solving the problem]

[0009] Means for Solving the Problems The present inventors, through extensive research, have discovered that by incorporating a specific alicyclic structure in a polycarbonate resin, a resin composition containing a polycarbonate resin (A) and an acrylic resin (B) can be obtained that has excellent properties such as transparency, heat resistance, low photoelastic coefficient, impact resistance, weather resistance, surface hardness and moist heat resistance, and have thus completed the present invention.

[0010] That is, according to the present invention, the object of the invention is achieved as follows.

[0011] 1. A resin composition comprising a polycarbonate resin (A) and an acrylic resin (B) containing 5 mol % or more and 90 mol % or less of repeating units (a) represented by the following formula (a) among all repeating units, and the weight ratio of the polycarbonate resin to the acrylic resin is 1:99 to 99:1.

[0012] [ka]

[0013] (In the formula, C mrepresents an alkylene group having a cyclic structure, and m represents an integer of 3 to 20. In addition, R represents an alkyl group having 1 to 20 carbon atoms or a cycloalkyl group having 3 to 10 carbon atoms, and n represents an integer of 1 to 10.

[0014] 2. The repeating unit (a) is represented by the following formula (a-1):

[0015] [ka]

[0016] (R 1 , R 2 , R 3 , R 4 are alkyl groups which may be the same or different, R 1 ~R 4 The total number of carbon atoms in R is 4 to 40. 1 and R 2 , R 3 and R 4 may be bonded to form a carbocyclic ring. 2. The resin composition according to item 1 above, wherein the repeating unit (a-1) is represented by the following formula:

[0017] 3.R 1 , R 2 , R 3 , R 4 and each of the above is a methyl group or an ethyl group.

[0018] 4. The resin composition according to any one of items 1 to 3 above, wherein the acrylic resin (B) contains a repeating unit (b) represented by the following formula (b) in an amount of 10 to 100 mol % based on all repeating units:

[0019] [ka]

[0020] (In the formula, R 5 represents a hydrogen atom or a methyl group, and R 6represents a branched or linear alkyl group having 1 to 20 carbon atoms or a cycloalkyl group having 6 to 20 carbon atoms which may have a substituent.

[0021] 5. The resin composition according to item 4 above, wherein the repeating unit (b) is a repeating unit (b) derived from methyl methacrylate and / or methyl acrylate. 6. The resin composition according to any one of items 1 to 5 above, which has a glass transition temperature of 90°C to 150°C. 7. The resin composition according to any one of items 1 to 6 above, wherein a haze of a test piece having a thickness of 7.2 mm is 20% or less. 8. The resin composition according to any one of items 1 to 7 above, which has a surface hardness of F or more. 9. Photoelastic coefficient is 60 x 10 -12 Pa -1 9. The resin composition according to any one of items 1 to 8 above, which is: 10. Charpy notched impact strength measured according to ISO 179 is 1.5KJ / m 2 10. The resin composition according to any one of items 1 to 9 above. 11. A molded article obtained by molding the resin composition according to any one of items 1 to 10 above. 12. A film or sheet formed from the resin composition according to any one of items 1 to 10 above. Effect of the Invention

[0022] The present invention makes it possible to provide a composition containing a polycarbonate resin and an acrylic resin, which has excellent properties such as transparency, heat resistance, low photoelastic coefficient, impact resistance, weather resistance, surface hardness, and moist heat resistance, by containing a specific alicyclic structure in the polycarbonate resin, and therefore has exceptional industrial effects. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0023] The present invention will be described in detail below.

[0024] <Polycarbonate resin (A)> The polycarbonate resin used in the resin composition of the present invention is a polycarbonate resin whose repeating unit contains a structure derived from an alicyclic diol having a side chain alkyl group or a side chain cycloalkyl group, as shown in the repeating unit (a) represented by the following formula (a).

[0025] [ka]

[0026] In the formula (a), C m represents an alkylene group having a cyclic structure containing 3 to 20 carbon atoms. The alkylene group having a cyclic structure containing 3 to 12 carbon atoms is preferred, the alkylene group having a cyclic structure containing 3 to 6 carbon atoms is more preferred, and the repeating unit is particularly preferably a cyclobutylene group having 4 carbon atoms, as shown in the repeating unit (a-1) represented by the following formula (a-1).

[0027] In the formula (a), R represents an alkyl group having 1 to 20 carbon atoms or a cycloalkyl group having 3 to 10 carbon atoms. Among the alkyl groups, an alkyl group having 1 to 8 carbon atoms is preferred, an alkyl group having 1 to 4 carbon atoms is more preferred, and an alkyl group having 1 to 2 carbon atoms is even more preferred. Examples of the alkyl group include a methyl group, an ethyl group, a propyl group, a butyl group, a pentyl group, a hexyl group, a heptyl group, and an octyl group. Among the cycloalkyl groups, a cycloalkyl group having 3 to 8 carbon atoms is preferred, and a cycloalkyl group having 4 to 6 carbon atoms is more preferred. Examples of the cycloalkyl group include a cyclopropyl group, a cyclobutyl group, a cyclopentyl group, a cyclohexyl group, a cycloheptyl group, and a cyclooctyl group. In the formula (a), n represents an integer of 1 to 10. n is preferably an integer of 2 to 8, and more preferably an integer of 4 to 6.

[0028] [ka]

[0029] In the formula (a-1), R 1 , R 2, R 3 , R 4 are alkyl groups which may be the same or different, R 1 ~R 4 The total number of carbon atoms in R is 4 to 40, preferably 4 to 32, more preferably 4 to 24, further preferably 4 to 16, and particularly preferably 4 to 8. 1 and R 2 , R 3 and R 4 may be bonded to form a carbon ring. Examples of the alkyl group include a methyl group, an ethyl group, a propyl group, a butyl group, a pentyl group, a hexyl group, a heptyl group, and an octyl group. Examples of the cycloalkyl group include a cyclopropyl group, a cyclobutyl group, a cyclopentyl group, a cyclohexyl group, a cycloheptyl group, and a cyclooctyl group.

[0030] Examples of the alicyclic diol from which the structure of the unit (a-1) is derived include diol compounds such as 2,2,4,4-tetramethyl-1,3-cyclobutanediol, 2,2,4,4-tetraethyl-1,3-cyclobutanediol, 2,2,4,4-tetrabutyl-1,3-cyclobutanediol, 2,2,4,4-tetrapropyl-1,3-cyclobutanediol, and 2,2,4,4-tetrahexyl-1,3-cyclobutanediol.

[0031] Particularly preferably, R 1 , R 2 , R 3 , R 4 is a methyl group or an ethyl group, 2,2,4,4-tetramethyl-1,3-cyclobutanediol, 2,2,4,4-tetraethyl- 1,3-cyclobutanediol is used. These compounds are obtained as a mixture of trans and cis isomers. The cis-trans mixture ratio in the present invention can be selected within a range that does not impair the effect.

[0032] The polycarbonate resin used in the resin composition of the present invention contains the repeating unit (a) represented by the above formula (a) in 5 mol % or more of the total repeating units, preferably 5 to 90 mol %, more preferably 10 to 88 mol %, even more preferably 15 to 86 mol %, and particularly preferably 15 to 85 mol %. When the unit (a) is within the above range, the resin composition does not become cloudy due to phase separation during extrusion or molding of the resin composition with the acrylic resin, and polymerization of the polycarbonate resin is easy without crystallization during polymerization, which is preferable.

[0033] The polycarbonate resin used in the resin composition of the present invention contains a repeating unit represented by the above formula (a), and is preferably used as a copolymer with another repeating unit (a-2).

[0034] The repeating unit (a-2) is preferably a carbonate unit derived from an aliphatic diol compound, another alicyclic diol compound, a heterocycle-containing diol compound or an aromatic dihydroxy compound.

[0035] Aliphatic diol compounds include 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,12-dodecanediol, 2-methyl-1,3-propanediol, neopentyl glycol, 3-methyl-1,5-pentanediol, 2-n-butyl-2-ethyl-1,3-propanediol, and 2,2-diethyl-1,3-propanediol. Examples of the diol include 2,4-diethyl-1,5-pentanediol, 1,2-hexane glycol, 1,2-octyl glycol, 2-ethyl-1,3-hexanediol, 2,3-diisobutyl-1,3-propanediol, 2,2-diisoamyl-1,3-propanediol, and 2-methyl-2-propyl-1,3-propanediol. Of these, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, and 1,12-dodecanediol are preferably used.

[0036] Other alicyclic diol compounds include cyclohexanediols such as 1,2-cyclohexanediol, 1,3-cyclohexanediol, 1,4-cyclohexanediol, and 2-methyl-1,4-cyclohexanediol; cyclohexanedimethanols such as 1,2-cyclohexanedimethanol, 1,3-cyclohexanedimethanol, and 1,4-cyclohexanedimethanol; norbornane dimethanols such as 2,3-norbornane dimethanol and 2,5-norbornane dimethanol; tricyclodecane dimethanol, pentacyclopentadecane dimethanol, 1,3-adamantanediol, 2,2-adamantanediol, and decalin dimethanol; and the like, with cyclohexanedimethanols being preferred.

[0037] Examples of heterocycle-containing diol compounds include 3,9-bis(2-hydroxy-1,1-dimethylethyl)-2,4,8,10-tetraoxaspiro[5.5]undecane, 2,2',1,1'-,1,1'-spirobiindane-6,6'-diol, isosorbide, isomannide, and isoidide, with isosorbide being preferred.

[0038] Aromatic dihydroxy compounds include α,α'-bis(4-hydroxyphenyl)-m-diisopropylbenzene (bisphenol M), 9,9-bis(4-hydroxy-3-methylphenyl)fluorene, and 1,1-bis(4-hydroxyphenyl)cyclohexane. , 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane (bisphenol TMC), 4,4'-dihydroxy-3,3'-dimethyldiphenyl sulfide, bisphenol A, 2,2-bis(4-hydroxy-3-methylphenyl)propane (bisphenol C), 2,2-bis(4-hydroxyphenyl)-1,1,1,3,3,3-hexafluoropropane (bisphenol AF), and 1,1-bis(4-hydroxyphenyl)decane, among which bisphenol A and bisphenol TMC are preferably used.

[0039] (Production method of polycarbonate resin) The polycarbonate resin is produced by a reaction means known per se for producing a normal polycarbonate resin, for example, a method of reacting a diol component with a carbonate precursor such as a carbonic acid diester. Next, the basic means for these production methods will be briefly described.

[0040] The transesterification reaction using a carbonic acid diester as a carbonate precursor is carried out by a method in which a predetermined ratio of diol components is heated and stirred with a carbonic acid diester under an inert gas atmosphere, and the alcohol or phenols produced are distilled off. The reaction temperature varies depending on the boiling point of the alcohol or phenols produced, but is usually in the range of 120 to 300°C. The reaction is completed by reducing the pressure from the beginning of the reaction to distill off the alcohol or phenols produced. In addition, a terminal terminator, an antioxidant, etc. may be added as necessary.

[0041] The carbonic acid diester used in the transesterification reaction includes esters of aryl groups and aralkyl groups having 6 to 12 carbon atoms, which may be substituted. Specific examples include diphenyl carbonate, ditolyl carbonate, bis(chlorophenyl) carbonate, and m-cresyl carbonate. Among these, diphenyl carbonate is particularly preferred. The amount of diphenyl carbonate used is preferably 0.97 to 1.10 mol, more preferably 1.00 to 1.06 mol, per mol of the total of the dihydroxy compounds.

[0042] In the melt polymerization method, a polymerization catalyst can be used to increase the polymerization rate. Examples of such a polymerization catalyst include alkali metal compounds, alkaline earth metal compounds, nitrogen-containing compounds, and metal compounds.

[0043] As such compounds, organic acid salts, inorganic salts, oxides, hydroxides, hydrides, alkoxides, quaternary ammonium hydroxides, etc. of alkali metals or alkaline earth metals are preferably used, and these compounds can be used alone or in combination.

[0044] Examples of alkali metal compounds include sodium hydroxide, potassium hydroxide, cesium hydroxide, lithium hydroxide, sodium hydrogen carbonate, sodium carbonate, potassium carbonate, cesium carbonate, lithium carbonate, sodium acetate, potassium acetate, cesium acetate, lithium acetate, sodium stearate, potassium stearate, cesium stearate, lithium stearate, sodium borohydride, sodium benzoate, potassium benzoate, cesium benzoate, lithium benzoate, disodium hydrogen phosphate, dipotassium hydrogen phosphate, dilithium hydrogen phosphate, disodium phenylphosphate, disodium salt, dipotassium salt, dicesium salt, and dilithium salt of bisphenol A, and sodium, potassium, cesium, and lithium salts of phenol.

[0045] Examples of alkaline earth metal compounds include magnesium hydroxide, calcium hydroxide, strontium hydroxide, barium hydroxide, magnesium carbonate, calcium carbonate, strontium carbonate, barium carbonate, magnesium diacetate, calcium diacetate, strontium diacetate, barium diacetate, and barium stearate.

[0046] Examples of the nitrogen-containing compound include quaternary ammonium hydroxides having an alkyl or aryl group, such as tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrapropylammonium hydroxide, tetrabutylammonium hydroxide, and trimethylbenzylammonium hydroxide. Other examples include tertiary amines, such as triethylamine, dimethylbenzylamine, and triphenylamine, and imidazoles, such as 2-methylimidazole, 2-phenylimidazole, and benzimidazole. Other examples include bases or basic salts, such as ammonia, tetramethylammonium borohydride, tetrabutylammonium borohydride, tetrabutylammonium tetraphenylborate, and tetraphenylammonium tetraphenylborate.

[0047] Examples of the metal compound include zinc aluminum compounds, germanium compounds, organotin compounds, antimony compounds, manganese compounds, titanium compounds, zirconium compounds, etc. These compounds may be used alone or in combination of two or more.

[0048] The amount of the polymerization catalyst used is preferably 1×10 -9 ~1×10 -2 equivalent, preferably 1 x 10 -8 ~1×10 -5 equivalent, more preferably 1×10 -7 ~1×10 -3 is selected within the equivalent range.

[0049] A catalyst deactivator can also be added in the later stage of the reaction. Known catalyst deactivators can be effectively used as the catalyst deactivator, and among these, ammonium salts and phosphonium salts of sulfonic acid are preferred. Furthermore, salts of dodecylbenzenesulfonic acid such as tetrabutylphosphonium dodecylbenzenesulfonate and salts of paratoluenesulfonic acid such as tetrabutylammonium paratoluenesulfonate are preferred.

[0050] As the ester of sulfonic acid, methyl benzenesulfonate, ethyl benzenesulfonate, butyl benzenesulfonate, octyl benzenesulfonate, phenyl benzenesulfonate, methyl paratoluenesulfonate, ethyl paratoluenesulfonate, butyl paratoluenesulfonate, octyl paratoluenesulfonate, phenyl paratoluenesulfonate, etc. are preferably used. Among them, tetrabutylphosphonium dodecylbenzenesulfonate is most preferably used.

[0051] When at least one polymerization catalyst selected from alkali metal compounds and / or alkaline earth metal compounds is used, the amount of these catalyst deactivators used is preferably 0.5 to 50 mol, more preferably 0.5 to 10 mol, and even more preferably 0.8 to 5 mol, per mol of the catalyst.

[0052] (Specific viscosity:η SP ) The specific viscosity (η SP ) is preferably 0.2 to 1.5. When the specific viscosity is in the range of 0.2 to 1.5, the strength and moldability of the molded product are good. It is more preferably 0.25 to 1.0, further preferably 0.28 to 0.8, and particularly preferably 0.3 to 0.5.

[0053] The specific viscosity referred to in the present invention is determined by using an Ostwald viscometer to measure a solution in which 0.7 g of polycarbonate resin is dissolved in 100 ml of methylene chloride at 20°C. Specific viscosity (η SP )=(tt 0 ) / t 0 [t 0 is the time it takes for methylene chloride to fall, and t is the time it takes for the sample solution to fall] The specific viscosity can be measured, for example, as follows. First, polycarbonate resin is dissolved in methylene chloride of 20 to 30 times its weight, and the soluble portion is collected by celite filtration. The solution is then removed and the mixture is thoroughly dried to obtain a solid soluble in methylene chloride. 0.7 g of the solid is dissolved in 100 ml of methylene chloride, and the specific viscosity at 20°C is determined using an Ostwald viscometer.

[0054] <Acrylic resin (B)> The structure of the acrylic resin used in the resin composition of the present invention is not particularly limited. Among the acrylic resins, acrylic resins containing a repeating unit (b) represented by the following formula (b) are preferred.

[0055] [ka]

[0056] (In the formula, R 5 represents a hydrogen atom or a methyl group, and R 6represents a branched or linear alkyl group having 1 to 20 carbon atoms or a cycloalkyl group having 6 to 20 carbon atoms which may have a substituent.

[0057] Examples of monomers that derive the repeating unit (b) represented by the formula (b) include compounds such as methyl methacrylate, methyl acrylate, benzyl (meth)acrylate, n-butyl (meth)acrylate, i-butyl (meth)acrylate, t-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, cyclohexyl (meth)acrylate, norbornyl (meth)acrylate, dicyclopentenyl (meth)acrylate, dicyclopentanyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, cyclopentyl methacrylate, cyclopentyl acrylate, cyclohexyl methacrylate, cyclohexyl acrylate, cycloheptyl methacrylate, cycloheptyl acrylate, cyclooctyl methacrylate, cyclooctyl acrylate, cyclododecyl methacrylate, and cyclododecyl acrylate.

[0058] Other examples of monomers that may be used include the following compounds: methacrylic acid, acrylic acid, lauryl (meth)acrylate, tridecyl (meth)acrylate, stearyl (meth)acrylate, glycidyl (meth)acrylate, hydroxypropyl (meth)acrylate, 2-methoxyethyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, isobornyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-(meth)acryloyloxyethyl succinate, 2-(meth)acryloyloxyethyl maleate, 2-(meth)acryloyloxyethyl phthalate, 2-(meth)acryloyloxyethyl hexahydrophthalate, pentamethylpiperidyl (meth)acrylate, tetramethylpiperidyl (meth)acrylate, dimethylaminoethyl (meth)acrylate, diethylaminoethyl (meth)acrylate, and the like.

[0059] These may be polymerized alone or in combination of two or more. Of these, it is preferable to use methyl methacrylate and / or methyl acrylate as the monomer from which the repeating unit (b) is derived, and it is particularly preferable to use methyl methacrylate.

[0060] The acrylic resin of the present invention preferably contains 10 to 100 mol %, more preferably 10 to 99 mol %, further preferably 30 to 95 mol %, and particularly preferably 50 to 90 mol % of the repeating units (b) based on the total repeating units. When the repeating units (b) are within the above range, the resin has excellent thermal decomposition resistance and is less likely to cause molding defects such as silver during molding. In addition, the heat distortion temperature is less likely to decrease. Furthermore, the repeating units (b) polymerized with these acrylic monomers are more likely to be polymerized with the acrylic monomers. Other monomers that can be used, such as polyolefin monomers and vinyl monomers, may also be used in combination.

[0061] The molecular weight of the acrylic resin is not particularly limited, but as long as the weight-average molecular weight is in the range of 30,000 or more and 300,000 or less, a composition that does not cause appearance defects such as flow unevenness during molding and has excellent mechanical properties and heat resistance can be provided.

[0062] The acrylic resin used in the resin composition of the present invention preferably has a specific viscosity in the range of 0.12 to 0.55. If the specific viscosity is less than 0.12, the molded product may become brittle. If the specific viscosity is higher than 0.55, the melt viscosity of the resin may increase, resulting in poor moldability.

[0063] The glass transition temperature (Tg) of the acrylic resin used in the present invention is preferably 90 to 150° C., more preferably 95 to 145° C., and further preferably 100 to 140° C. When Tg is 90 to 150° C., good heat resistance stability and moldability are obtained, which is preferable. The glass transition temperature (Tg) is measured using a 2910 model DSC manufactured by TA Instruments Japan, Inc. at a heating rate of 20°C / min.

[0064] The acrylic resin used in the present invention is not particularly limited, but is preferably an acrylic resin having a melt flow rate of 0.5 to 30 g / 10 min measured at 230° C. under a load of 3.8 kg in accordance with JIS K7210. More preferably, the melt flow rate is 0.7 to 27 g / 10 min, and even more preferably, the melt flow rate is 1.0 to 25 g / 10 min. An acrylic resin having a melt flow rate in this range has good moldability.

[0065] <Method for producing a resin composition containing a polycarbonate resin and an acrylic resin> The resin composition of the present invention is preferably prepared by blending a polycarbonate resin and an acrylic resin in a molten state. As a method for blending in a molten state, an extruder is generally used, and the molten resin is kneaded at a molten resin temperature of 200 to 320°C, preferably 220 to 300°C, more preferably 230 to 290°C, and then pelletized. This provides pellets of a resin composition in which both resins are uniformly blended. The configuration of the extruder, the configuration of the screw, and the like are not particularly limited. If the molten resin temperature in the extruder exceeds 320°C, the resin may become discolored or may undergo thermal decomposition. On the other hand, if the resin temperature is below 200°C, the resin viscosity may be too high, causing an overload on the extruder.

[0066] (weight ratio) The weight ratio of the polycarbonate resin to the acrylic resin can be arbitrarily mixed within the range of 1:99 to 99:1. The range is preferably 5:95 to 98:2, more preferably 10:90 to 97:3, still more preferably 20:80 to 96:4, and particularly preferably 30:70 to 95:5. By adjusting the ratio within the above range, a resin composition having excellent heat resistance and impact resistance can be obtained.

[0067] (Glass transition temperature: Tg) The resin composition of the present invention preferably has a single glass transition temperature (Tg), and the glass transition temperature (Tg) is preferably 90 to 150° C., more preferably 100 to 145° C., and further preferably 110 to 140° C. If the Tg is within the above range, the composition has good heat resistance stability and moldability when used as an optical molded article, which is preferable.

[0068] The glass transition temperature (Tg) is measured at a heating rate of 20° C. / min using a 2910 DSC manufactured by TA Instruments Japan Co., Ltd. In the present invention, a single glass transition temperature (Tg) means that when the glass transition temperature is measured using a differential scanning calorimeter (DSC) at a heating rate of 20° C. / min in accordance with JIS K7121, only one inflection point indicating the glass transition temperature appears.

[0069] Generally, when a polymer blend composition has a single glass transition temperature, it means that the mixed resins are in a compatible state on the nanometer order (molecular level), and the system can be considered to be compatible.

[0070] (Pencil hardness) The resin composition of the present invention preferably has a pencil hardness (surface hardness) of F or more. In terms of excellent scratch resistance, it is more preferable that the hardness is H or more. The pencil hardness is sufficient with a pencil hardness of 4H or less. The pencil hardness can be increased by increasing the weight ratio of the acrylic resin. In the present invention, the pencil hardness refers to a hardness at which no scratch marks are left when the resin of the present invention is rubbed with a pencil having a specific pencil hardness, and it is preferable to use the pencil hardness used in the surface hardness test of the coating film that can be measured according to JIS K-5600 as an index. The pencil hardness becomes softer in the order of 9H, 8H, 7H, 6H, 5H, 4H, 3H, 2H, H, F, HB, B, 2B, 3B, 4B, 5B, and 6B, with the hardest being 9H and the softest being 6B.

[0071] (Additives) The resin composition used in the present invention may contain additives such as a heat stabilizer, a plasticizer, a light stabilizer, a polymerized metal deactivator, a flame retardant, a lubricant, an antistatic agent, a surfactant, an antibacterial agent, an ultraviolet absorber, a release agent, and a colorant, depending on the application and need.

[0072] (Heat stabilizer) The resin composition used in the present invention preferably contains a heat stabilizer in particular in order to suppress the decrease in molecular weight and the deterioration of color during extrusion and molding. Examples of the heat stabilizer include phosphorus-based heat stabilizers, phenol-based heat stabilizers, and sulfur-based heat stabilizers, and these can be used alone or in combination of two or more. It is preferable to blend a phosphite compound as the phosphorus-based stabilizer. Examples of the phosphite compound include pentaerythritol-type phosphite compounds, phosphite compounds that react with dihydric phenols and have a cyclic structure, and phosphite compounds having other structures.

[0073] Specific examples of the pentaerythritol phosphite compound include distearyl pentaerythritol diphosphite, bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite, bis(2,6-di-tert-butyl-4-methylphenyl)pentaerythritol diphosphite, bis(2,6-di-tert-butyl-4-ethylphenyl)pentaerythritol diphosphite, phenyl bisphenol A pentaerythritol diphosphite, bis(nonylphenyl)pentaerythritol diphosphite, dicyclohexyl pentaerythritol diphosphite, and the like. Among these, distearyl pentaerythritol diphosphite and bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite are preferred.

[0074] Examples of the phosphite compounds having a cyclic structure upon reaction with the above dihydric phenols include 2,2'-methylenebis(4,6-di-tert-butylphenyl)(2,4-di-tert-butylphenyl)phosphite, 2,2'-methylenebis(4,6-di-tert-butylphenyl)(2-tert-butyl-4-methylphenyl)phosphite, 2,2'-methylenebis(4-methyl-6-tert-butylphenyl)(2-tert-butyl-4-methylphenyl)phosphite, 2,2'-ethylidenebis(4-methyl-6-tert-butylphenyl)(2-tert-butyl-4-methylphenyl)phosphite, phosphite, 2,2'-methylene-bis-(4,6-di-t-butylphenyl)octyl phosphite, 6-tert-butyl-4-[3-[(2,4,8,10)-tetra-tert-butyldibenzo[d,f][1,3,2]dioxaphosphepin-6-yl)oxy]propyl]-2-methylphenol, and the like.

[0075] Examples of phosphite compounds having the above other structures include triphenyl phosphite, tris(nonylphenyl)phosphite, tridecyl phosphite, trioctyl phosphite, trioctadecyl phosphite, didecyl monophenyl phosphite, dioctyl monophenyl phosphite, diisopropyl monophenyl phosphite, monobutyl diphenyl phosphite, monodecyl diphenyl phosphite, monooctyl diphenyl phosphite, 2,2-methylenebis(4,6-di-tert-butylphenyl)octyl phosphite, tris(diethylphenyl)phosphite, tris(di-isopropylphenyl)phosphite, tris(di-n-butylphenyl)phosphite, tris(2,4-di-tert-butylphenyl)phosphite, and tris(2,6-di-tert-butylphenyl)phosphite.

[0076] In addition to the various phosphite compounds, examples of the compounds include phosphate compounds, phosphonite compounds, and phosphonate compounds.

[0077] Examples of the phosphate compound include tributyl phosphate, trimethyl phosphate, tricresyl phosphate, triphenyl phosphate, trichlorophenyl phosphate, triethyl phosphate, diphenyl cresyl phosphate, diphenyl monoorthoxenyl phosphate, tributoxyethyl phosphate, dibutyl phosphate, dioctyl phosphate, diisopropyl phosphate, and the like, and preferably triphenyl phosphate and trimethyl phosphate.

[0078] Examples of the phosphonite compounds include tetrakis(2,4-di-tert-butylphenyl)-4,4'-biphenylene diphosphonite, tetrakis(2,4-di-tert-butylphenyl)-4,3'-biphenylene diphosphonite, tetrakis(2,4-di-tert-butylphenyl)-3,3'-biphenylene diphosphonite, tetrakis(2,6-di-tert-butylphenyl)-4,4'-biphenylene diphosphonite, tetrakis(2,6-di-tert-butylphenyl)-4,3'-biphenylene diphosphonite, tetrakis(2,6-di-tert-butylphenyl)-3,3'-biphenylene diphosphonite, bis(2,4-di-tert-butylphenyl)-4-phenyl-phenylphosphonite, bis Examples of the phosphonite include (2,4-di-tert-butylphenyl)-3-phenyl-phenylphosphonite, bis(2,6-di-n-butylphenyl)-3-phenyl-phenylphosphonite, bis(2,6-di-tert-butylphenyl)-4-phenyl-phenylphosphonite, and bis(2,6-di-tert-butylphenyl)-3-phenyl-phenylphosphonite. Tetrakis(di-tert-butylphenyl)-biphenylene diphosphonite and bis(di-tert-butylphenyl)-phenyl-phenylphosphonite are preferred, and tetrakis(2,4-di-tert-butylphenyl)-biphenylene diphosphonite and bis(2,4-di-tert-butylphenyl)-phenyl-phenylphosphonite are more preferred. Such phosphonite compounds can be used in combination with the phosphite compounds having an aryl group substituted with two or more alkyl groups, and are therefore preferred.

[0079] Examples of the phosphonate compound include dimethyl benzenephosphonate, diethyl benzenephosphonate, and dipropyl benzenephosphonate.

[0080] Among the above phosphorus-based heat stabilizers, tris(nonylphenyl) phosphite, trimethyl phosphate, tris(2,4-di-tert-butylphenyl) phosphite, bis(2, Preferably used are bis(2,6-di-tert-butyl-4-methylphenyl)pentaerythritol diphosphite and bis(2,6-di-tert-butyl-4-methylphenyl)pentaerythritol diphosphite.

[0081] The phosphorus-based heat stabilizers can be used alone or in combination of two or more kinds. The phosphorus-based heat stabilizer is preferably blended in an amount of 0.001 to 1 part by weight, more preferably 0.01 to 0.5 parts by weight, and even more preferably 0.01 to 0.3 parts by weight per 100 parts by weight of the resin composition.

[0082] In order to suppress the decrease in molecular weight and deterioration of color during extrusion and molding, the resin composition used in the present invention may also contain a heat stabilizer such as a hindered phenol-based heat stabilizer or a sulfur-based heat stabilizer in combination with a phosphorus-based heat stabilizer.

[0083] The hindered phenol-based heat stabilizer is not particularly limited as long as it has an antioxidant function. Examples of the hindered phenol-based heat stabilizer include n-octadecyl-3-(4'-hydroxy-3',5'-di-t-butylphenyl)propionate, tetrakis{methylene-3-(3',5'-di-t-butyl-4-hydroxyphenyl)propionate}methane, distearyl(4-hydroxy-3-methyl-5-t-butylbenzyl)malonate, triethylene glycol-bis{3-(3-t-butyl-5-methyl-4-hydroxyphenyl)propionate}, 1,6-hexanediol-bis{3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate}, pentaerythrityl-tetrakis{3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate}, 2,2- Thiodiethylene bis{3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate}, 2,2-thiobis(4-methyl-6-t-butylphenol), 1,3,5-trimethyl-2,4,6-tris(3,5-di-t-butyl-4-hydroxybenzyl)benzene, tris(3,5-di-t-butyl-4-hydroxybenzyl)isocyanurate, 2,4-bis{(octyl thio)methyl}-o-cresol, isooctyl-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate, 2,5,7,8-tetramethyl-2(4',8',12'-trimethyltridecyl)chroman-6-ol, 3,3',3",5,5',5"-hexa-t-butyl-a,a',a"-(mesitylene-2,4,6-triyl)tri-p-cresol, and the like.

[0084] Among these, n-octadecyl-3-(4'-hydroxy-3',5'-di-t-butylphenyl)propionate, pentaerythrityl-tetrakis{3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate}, 3,3',3",5,5',5"-hexa-t-butyl-a,a',a'-(mesitylene-2,4,6-triyl)tri-p-cresol, 2,2-thiodiethylenebis{3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate}, and the like are preferred.

[0085] These hindered phenol-based heat stabilizers may be used alone or in combination of two or more. The hindered phenol-based heat stabilizer is preferably blended in an amount of 0.001 to 1 part by weight, more preferably 0.01 to 0.5 parts by weight, and even more preferably 0.01 to 0.3 parts by weight, per 100 parts by weight of the resin composition.

[0086] Examples of sulfur-based heat stabilizers include dilauryl-3,3'-thiodipropionate, ditridecyl-3,3'-thiodipropionate, dimyristyl-3,3'-thiodipropionate, distearyl-3,3'-thiodipropionate, laurylstearyl-3,3'-thiodipropionate, pentaerythritol tetrakis(3-laurylthiopropionate), bis[2-methyl-4-(3-laurylthiopropionyloxy)-5-tert-butylphenyl]sulfide, octadecyl disulfide, mercaptobenzimidazole, 2-mercapto-6-methylbenzimidazole, 1,1'-thiobis(2-naphthol), etc. Among the above, pentaerythritol tetrakis(3-laurylthiopropionate) is preferred.

[0087] These sulfur-based heat stabilizers may be used alone or in combination of two or more kinds. The sulfur-based heat stabilizer is preferably blended in an amount of 0.001 to 1 part by weight, more preferably 0.01 to 0.5 parts by weight, and even more preferably 0.01 to 0.3 parts by weight, per 100 parts by weight of the resin composition.

[0088] When a phosphite-based heat stabilizer, a phenol-based heat stabilizer, and a sulfur-based heat stabilizer are used in combination, the total amount of these is preferably 0.001 to 1 part by weight, more preferably 0.01 to 0.3 part by weight, per 100 parts by weight of the resin composition.

[0089] (Release agent) The resin composition used in the present invention may contain a mold release agent in order to further improve releasability from a mold during melt molding, within the scope of the present invention.

[0090] Examples of such release agents include higher fatty acid esters of monohydric or polyhydric alcohols, higher fatty acids, paraffin wax, beeswax, olefin waxes, olefin waxes containing carboxy groups and / or carboxylic anhydride groups, silicone oils, and organopolysiloxanes.

[0091] The higher fatty acid ester is preferably a partial or full ester of a monohydric or polyhydric alcohol having 1 to 20 carbon atoms and a saturated fatty acid having 10 to 30 carbon atoms. Examples of such partial or full esters of a monohydric or polyhydric alcohol and a saturated fatty acid include stearic acid monoglyceride, stearic acid diglyceride, stearic acid triglyceride, stearic acid monosorbitate, stearyl stearate, behenic acid monoglyceride, behenyl behenate, pentaerythritol monostearate, pentaerythritol tetrastearate, pentaerythritol tetrapelargonate, propylene glycol monostearate, stearyl stearate, palmityl palmitate, butyl stearate, methyl laurate, isopropyl palmitate, biphenyl biphenate, sorbitan monostearate, and 2-ethylhexyl stearate. Of these, stearic acid monoglyceride, stearic acid triglyceride, pentaerythritol tetrastearate, and behenyl behenate are preferably used.

[0092] The higher fatty acid is preferably a saturated fatty acid having a carbon number of 10 to 30. Examples of such fatty acids include myristic acid, lauric acid, palmitic acid, stearic acid, and behenic acid. These release agents may be used alone or in combination of two or more. The amount of such release agent to be added is preferably 0.01 to 5 parts by weight based on 100 parts by weight of the resin composition.

[0093] (UV absorber) The resin composition used in the present invention may contain an ultraviolet absorber. Examples of the ultraviolet absorber include benzotriazole-based ultraviolet absorbers, benzophenone-based ultraviolet absorbers, triazine-based ultraviolet absorbers, cyclic iminoester-based ultraviolet absorbers, and cyanoacrylate-based ultraviolet absorbers, and among these, benzotriazole-based ultraviolet absorbers are preferred.

[0094] Examples of the benzotriazole-based ultraviolet absorbers include 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 2-(2'-hydroxy-5'-tert-butylphenyl)benzotriazole, 2-(2'-hydroxy-5'-tert-octylphenyl)benzotriazole, 2-(2'-hydroxy-3',5'-di-tert-butylphenyl)benzotriazole, 2-(2'-hydroxy-3',5'-di-tert-amylphenyl)benzotriazole, 2-(2'-hydroxy-3'-dodecyl-5'-methylphenyl)benzotriazole, 2-(2'-hydroxy-3',5'-bis(α,α'-dimethylbenzyl)phenylbenzotriazole, 2-[2'-hydroxy benzotriazole-based ultraviolet absorbers represented by 2-(2'-hydroxy-3'-tert-butyl-5'-methylphenyl)-5-chlorobenzotriazole, 2-(2'-hydroxy-3',5'-di-tert-butylphenyl)-5-chlorobenzotriazole, 2,2'methylenebis[4-(1,1,3,3-tetramethylbutyl)-6-(2H-benzotriazol-2-yl)phenol], and methyl-3-[3-tert-butyl-5-(2H-benzotriazol-2-yl)-4-hydroxyphenylpropionate-polyethylene glycol condensate can be mentioned.

[0095] The proportion of such an ultraviolet absorber is preferably 0.01 to 2 parts by weight, more preferably 0.1 to 1 part by weight, and further preferably 0.2 to 0.5 parts by weight, based on 100 parts by weight of the resin composition.

[0096] (Light stabilizer) The resin composition used in the present invention may contain a light stabilizer. The inclusion of a light stabilizer has the advantages of being excellent in terms of weather resistance and making the molded product less susceptible to cracking.

[0097] Examples of the light stabilizer include 1,2,2,6,6-pentamethyl-4-piperidyl methacrylate, didecanoic acid bis(2,2,6,6-tetramethyl-1-octyloxy-4-piperidinyl) ester, bis(1,2,2,6,6-pentamethyl-4-piperidinyl)-[[3,5-bis(1,1-dimethylethyl)-4-hydroxyphenyl]methyl]butyl malonate, 2,4-bis[N-butyl-N-(1-cyclohexyloxy-2,2,6,6 -tetramethylpiperidin-2-yl)amino]-6-(2-hydroxyethylamine)-1,3,5-triazine, bis(1,2,2,6,6-pentamethyl-4-piperidinyl) sebacate, methyl(1,2,2,6,6-pentamethyl-4-piperidinyl) sebacate, bis(2,2,6,6-tetramethyl-4-piperidyl) carbonate, bis(2,2,6,6-tetramethyl-4-piperidyl) succinate, bis(2,2,6,6-tetramethyl 4-benzoyloxy-2,2,6,6-tetramethylpiperidine, 4-octanoyloxy-2,2,6,6-tetramethylpiperidine, bis(2,2,6,6-tetramethyl-4-piperidyl)diphenylmethane-p,p′-dicarbamate, bis(2,2,6,6-tetramethyl-4-piperidyl)benzene-1,3-disulfonate, bis(2,2,6,6-tetramethyl-4-piperidyl)phenylphosphine Examples of the light stabilizer include hindered amines such as thiophene, nickel bis(octylphenyl sulfide), nickel complex-3,5-di-t-butyl-4-hydroxybenzyl phosphate monoethylate, and nickel complexes such as nickel dibutyldithiocarbamate. These light stabilizers may be used alone or in combination of two or more. The content of the light stabilizer is preferably 0.001 to 1 part by weight, and more preferably 0.01 to 0.5 parts by weight, based on 100 parts by weight of the resin composition.

[0098] (Epoxy stabilizer) The resin composition used in the present invention may include a compound having a hydrolyzability that is not compatible with the object of the present invention. An epoxy compound can be blended as long as it does not cause any damage.

[0099] Epoxy stabilizers include epoxidized soybean oil, epoxidized linseed oil, phenyl glycidyl ether, allyl glycidyl ether, t-butylphenyl glycidyl ether, 3,4-epoxycyclohexylmethyl-3',4'-epoxycyclohexyl carboxylate, 3,4-epoxy-6-methylcyclohexylmethyl-3',4'-epoxy-6'-methylcyclohexyl carboxylate, 2,3-epoxycyclohexylmethyl-3',4'-epoxycyclohexyl carboxylate, 4-(3,4-epoxy-5-methylcyclohexyl) ... butyl-3',4'-epoxycyclohexyl carboxylate, 3,4-epoxycyclohexylethylene oxide, cyclohexylmethyl-3,4-epoxycyclohexyl carboxylate, 3,4-epoxy-6-methylcyclohexylmethyl-6'-methylcyclohexyl carboxylate, bisphenol A diglycidyl ether, tetrabromobisphenol A glycidyl ether, diglycidyl ester of phthalic acid, diglycidyl ester of hexahydrophthalic acid, bis-epoxydicyclopentadienyl ether, bis-epoxyethylene ethylene glycol, bis-epoxycyclohexyl adipate, butadiene diepoxide, tetraphenylethylene epoxide, octyl epoxy thalate, epoxidized polybutadiene, 3,4-dimethyl-1,2-epoxycyclohexane, 3,5-dimethyl-1,2-epoxycyclohexane, 3-methyl-5-t-butyl-1,2-epoxycyclohexane, octadecyl-2,2-dimethyl-3,4-epoxycyclohexyl carboxylate, N-butyl-2,2-dimethyl-3,4-epoxycyclohexyl carboxylate, cyclohexyl- 2-Methyl-3,4-epoxycyclohexyl carboxylate, N-butyl-2-isopropyl-3,4-epoxy-5-methylcyclohexyl carboxylate, octadecyl-3,4-epoxycyclohexyl carboxylate, 2-ethylhexyl-3',4'-epoxycyclohexyl carboxylate, 4,6-dimethyl-2,3-epoxycyclohexyl-3',4'-epoxycyclohexyl carboxylate, 4,5-epoxy tetrahydrophthalic anhydride, 3-t-butyl-4,5-epoxy tetrahydrophthalic anhydride, diethyl-4,5-epoxy-cis-1,2-cyclohexyl dicarboxylate, di-n-butyl-3-t-butyl-4,5-epoxy-cis-1,2-cyclohexyl dicarboxylate, etc. Bisphenol A diglycidyl ether is preferred from the viewpoint of compatibility, etc.

[0100] Such an epoxy stabilizer is desirably blended in an amount of 0.0001 to 5 parts by weight, preferably 0.001 to 1 part by weight, and more preferably 0.005 to 0.5 parts by weight, relative to 100 parts by weight of the resin composition.

[0101] (Bluing agent) The resin composition used in the present invention can be blended with a bluing agent to eliminate the yellow color of the lens due to the polymer or ultraviolet absorbing agent. As the bluing agent, any agent that is used for polycarbonate can be used without any problem. In general, anthraquinone dyes are easily available and are preferred.

[0102] Specific examples of bluing agents include those having the general name Solvent Violet 13 [CA. No (Color Index No) 60725], those having the general name Solvent Violet 31 [CA. No 68210, those having the general name Solvent Violet 33 [CA. No 60725], those having the general name Solvent Blue 94 [CA. No 61500], those having the general name Solvent Violet 36 [CA. No 68210], those having the general name Solvent Blue 97 [Bayer's "Macrolex Violet RR"], and those having the general name Solvent Blue 45 [CA. No 61110].

[0103] These bluing agents may be used alone or in combination of two or more. The bluing agent is preferably used in an amount of 0.1×10 -4 ~2×10 -4 It is mixed in parts by weight.

[0104] (Flame retardant) The resin composition used in the present invention may also contain a flame retardant. Examples of the flame retardant include halogen-based flame retardants such as brominated epoxy resin, brominated polystyrene, brominated polycarbonate, brominated polyacrylate, and chlorinated polyethylene, phosphate-based flame retardants such as monophosphate compounds and phosphate oligomer compounds, organic phosphorus-based flame retardants other than phosphate-based flame retardants such as phosphinate compounds, phosphonate compounds, phosphonitrile oligomer compounds, and phosphonic acid amide compounds, organic metal salt-based flame retardants such as organic sulfonic acid alkali (earth) metal salts, boric acid metal salt-based flame retardants, and stannic acid metal salt-based flame retardants, as well as silicone-based flame retardants, ammonium polyphosphate-based flame retardants, and triazine-based flame retardants. In addition, flame retardant assistants (e.g., sodium antimonate, antimony trioxide, etc.) and drip prevention agents (polytetrafluoroethylene having fibril forming ability, etc.) may be added separately and used in combination with the flame retardant.

[0105] Among the above-mentioned flame retardants, compounds that do not contain chlorine atoms or bromine atoms are more suitable as flame retardants for the molded article of the present invention, which is also characterized by reduced environmental impact, since they reduce factors that are considered undesirable when incinerating or thermally recycling the compounds.

[0106] When a flame retardant is added, the amount is preferably in the range of 0.05 to 50 parts by weight per 100 parts by weight of the resin composition. If the amount is less than 0.05 parts by weight, sufficient flame retardancy is not exhibited, and if the amount is more than 50 parts by weight, the strength and heat resistance of the molded product are impaired.

[0107] (Elastic polymer) In the resin composition used in the present invention, an elastic polymer can be used as an impact improver, and examples of the elastic polymer include graft copolymers in which one or more monomers selected from aromatic vinyl, vinyl cyanide, acrylic acid ester, methacrylic acid ester, and vinyl compounds copolymerizable therewith are copolymerized with natural rubber or a rubber component having a glass transition temperature of 10° C. or less. A more suitable elastic polymer is a core-shell type graft copolymer in which one or more shells of the above monomers are graft copolymerized with a core of a rubber component.

[0108] Also included are block copolymers of such rubber components and the above monomers. Specific examples of such block copolymers include thermoplastic elastomers such as styrene-ethylene-propylene-styrene elastomers (hydrogenated styrene-isoprene-styrene elastomers) and hydrogenated styrene-butadiene-styrene elastomers. Furthermore, it is also possible to use various elastic polymers known as other thermoplastic elastomers, such as polyurethane elastomers, polyester elastomers, polyetheramide elastomers, etc.

[0109] A core-shell type graft copolymer is more suitable as the elastic polymer. In the core-shell type graft copolymer, the particle diameter of the core is preferably 0.05 to 0.8 μm, more preferably 0.1 to 0.6 μm, and even more preferably 0.1 to 0.5 μm, in terms of weight average particle diameter. If it is in the range of 0.05 to 0.8 μm, better impact resistance is achieved. The elastic polymer preferably contains 40% or more of a rubber component, and even more preferably contains 60% or more.

[0110] Examples of the rubber component include butadiene rubber, butadiene-acrylic composite rubber, acrylic rubber, acrylic-silicone composite rubber, isobutylene-silicone composite rubber, isoprene rubber, styrene-butadiene rubber, chloroprene rubber, ethylene-propylene rubber, nitrile rubber, ethylene-acrylic rubber, silicone rubber, epichlorohydrin rubber, fluororubber, and those in which hydrogen has been added to the unsaturated bonds of these rubber components. However, due to concerns about the generation of harmful substances during combustion, rubber components that do not contain halogen atoms are preferred in terms of environmental impact.

[0111] The glass transition temperature of the rubber component is preferably -10°C or lower, more preferably -30°C or lower, and the rubber component is particularly preferably butadiene rubber, butadiene-acrylic composite rubber, acrylic rubber, or acrylic-silicone composite rubber. Composite rubber refers to rubber in which two types of rubber components are copolymerized, or rubber polymerized to form an IPN structure in which the components are mutually entangled so as not to be separated.

[0112] Examples of aromatic vinyls in the vinyl compounds copolymerized with the rubber component include styrene, α-methylstyrene, p-methylstyrene, alkoxystyrene, and halogenated styrene, with styrene being particularly preferred. Examples of acrylic esters include methyl acrylate, ethyl acrylate, butyl acrylate, cyclohexyl acrylate, and octyl acrylate, with methyl methacrylate being particularly preferred. Among these, it is preferable to contain methacrylic esters such as methyl methacrylate as an essential component. More specifically, the methacrylic ester is preferably contained in an amount of 10% by weight or more, more preferably 15% by weight or more, based on 100% by weight of the graft component (100% by weight of the shell in the case of a core-shell polymer).

[0113] The elastic polymer containing a rubber component having a glass transition temperature of 10°C or less may be produced by any of the polymerization methods of bulk polymerization, solution polymerization, suspension polymerization, and emulsion polymerization, and the copolymerization method may be either one-stage grafting or multi-stage grafting. The copolymer may also be a mixture with a copolymer of only the graft component that is a by-product during production. In addition to the general emulsion polymerization method, examples of the polymerization method include a soap-free polymerization method using an initiator such as potassium persulfate, a seed polymerization method, and a two-stage swelling polymerization method. In the suspension polymerization method, the aqueous phase and the monomer phase are held separately and accurately fed to a continuous disperser, and the particle size is controlled by the rotation speed of the disperser, and in the continuous production method, the monomer phase is fed into an aqueous liquid having dispersibility through a fine orifice or a porous filter having a diameter of several to several tens of μm to control the particle size. In the case of a core-shell type graft polymer, the reaction may be one-stage or multi-stage for both the core and the shell.

[0114] Such elastic polymers are commercially available and can be easily obtained. For example, examples of rubber components mainly composed of butadiene rubber, acrylic rubber, or butadiene-acrylic composite rubber include Kaneace B series (e.g., B-56, etc.) from Kanegafuchi Chemical Industry Co., Ltd., Metablen C series (e.g., C-223A, etc.) and W series (e.g., W-450A, etc.) from Mitsubishi Rayon Co., Ltd., Paraloid EXL series (e.g., EXL-2602, etc.), HIA series (e.g., HIA-15, etc.), BTA series (e.g., BTA-III, etc.), and KCA series from Kureha Chemical Industry Co., Ltd., Paraloid EXL series and KM series (e.g., KM-336P, KM-357P, etc.) from Rohm and Haas Co., Ltd., and UCL Modifier Resin series from Ube Cycon Co., Ltd. (UMG ABS Co., Ltd.), AXS resin series), and examples of rubber components that are primarily made of acrylic-silicone composite rubber include those sold by Mitsubishi Rayon Co., Ltd. under the trade names Metablen S-2001 and SRK-200.

[0115] The blending ratio of the elastic polymer is preferably 0.2 to 50 parts by weight, more preferably 1 to 30 parts by weight, and more preferably 1.5 to 20 parts by weight, per 100 parts by weight of the resin composition. This composition range can impart good impact resistance to the composition while suppressing a decrease in rigidity.

[0116] (molded product) The resin composition of the present invention can be molded and processed by any method such as injection molding, compression molding, injection compression molding, melt film forming, casting, etc., and can be used as molded products such as optical lenses, optical disks, optical films, plastic cell substrates, optical cards, liquid crystal panels, headlamp lenses, light guide plates, diffusion plates, protective films, OPC binders, front panels, housings, trays, water tanks, lighting covers, signboards, plastic windows, etc. Among these, it is preferably used as an injection molded product, sheet or film, and can be particularly used as a member requiring high surface hardness such as a front panel, housing, tray, water tank, lighting cover, signboard, plastic window, etc.

[0117] (transparency) The haze of a 2 mm thick molded piece of the resin composition of the present invention is preferably 20% or less, more preferably 15% or less, even more preferably 10% or less, and particularly preferably 5% or less. If the haze is within the above range, the range of use as an optical component is not limited, which is preferable.

[0118] (Photoelastic constant) The resin composition of the present invention is suitably used as an optical film, and the absolute value of the photoelastic constant of the resin composition is 60×10 -12 Pa -1 Less than or equal to 30×10 -12 Pa -1 Less than 20×10 is preferable. -12 Pa -1 Less than 15×10 is even better. -12 Pa -1 Particularly preferred is an absolute value of the photoelastic constant of 60×10 -12 Pa -1 If it is larger, the birefringence due to stress becomes large, and light leakage tends to occur when the film is used as a retardation film.

[0119] (Impact strength) The resin composition of the present invention has a notched Charpy impact strength of 1.5 KJ / m, measured according to ISO 179. 2 It is preferable that the concentration is 2KJ / m or more. 2 More preferably, it is 3KJ / m or more. 2 More preferably, the notched Charpy impact strength is 100KJ / m or more. 2 The following functions are sufficient.

[0120] (Surface treatment) Molded articles formed from the resin composition of the present invention can be subjected to various surface treatments. The surface treatment referred to here is a method for forming a new layer on the surface of a resin molded article, such as vapor deposition (physical vapor deposition, chemical vapor deposition, etc.), plating (electroplating, electroless plating, hot-dip plating, etc.), painting, coating, printing, etc., and any commonly used method can be applied. Specific examples of the surface treatment include various surface treatments such as hard coating, water-repellent / oil-repellent coating, ultraviolet absorbing coating, infrared absorbing coating, and metallizing (vapor deposition, etc.). Hard coating is a particularly preferred and necessary surface treatment. EXAMPLES

[0121] The present invention will be described in detail below with reference to examples, but the present invention is not limited thereto. In the examples, "parts" means "parts by weight." The resins and evaluation methods used in the examples are as follows.

[0122] 1. Polymer composition ratio (NMR) Each repeating unit was measured by proton NMR using a JNM-AL400 manufactured by JEOL Ltd., and the polymer composition ratio (molar ratio) was calculated.

[0123] 2. Specific viscosity The viscosity was measured using an Ostwald viscometer from a solution of 0.7 g of polycarbonate resin dissolved in 100 ml of methylene chloride at 20°C. Specific viscosity (η SP )=(tt0 ) / t 0 [t 0 is the time it takes for methylene chloride to fall, and t is the time it takes for the sample solution to fall]

[0124] 3. Glass transition temperature (Tg) Using 8 mg of the resin composition pellets, a thermal analysis system DSC-2910 manufactured by TA Instruments was used to perform the measurement in accordance with JIS K7121 under conditions of a nitrogen atmosphere (nitrogen flow rate: 40 ml / min) and a heating rate of 20°C / min.

[0125] 4. Hayes A 2 mm thick portion of a three-stage plate prepared by injection molding from the resin composition pellets was measured using a haze meter 300A manufactured by Nippon Denshoku Industries Co., Ltd.

[0126] 5.Pencil hardness (surface hardness) Based on JIS K5600, a test piece was prepared by injection molding resin composition pellets in a temperature-controlled room at an atmospheric temperature of 23°C. A line was drawn on the surface of the test piece with a pencil held at a 45° angle and a load of 750 g, and the surface condition was visually evaluated.

[0127] 6. Photoelastic constant The photoelastic constant was measured by dissolving the resin composition pellets in methylene chloride, evaporating the methylene chloride to obtain a cast film with a thickness of 200 μm, drying the film at 100° C. for 12 hours, cutting out a test piece with a length of 50 mm and a width of 10 mm, and using a Spectroellipsometer M-220 manufactured by JASCO Corporation.

[0128] 7. Weather-resistant discoloration In accordance with JIS B7753, a Sunshine Weatherometer S80 manufactured by Suga Test Instruments was used, and the discharge voltage was set to 50 V and the discharge current to 60 A with a Sunshine Carbon Arc (Ultra Long Life Carbon 4 pairs) light source. Irradiation and surface spray (rainfall) were performed for 500 hours on the square surface of a flat plate (width 60 mm × length 60 mm × thickness 3 mm) of a test piece made by injection molding from a resin composition pellet under conditions of a black panel temperature of 63 ° C and a relative humidity of 50%. The surface spray (rainfall) time was 12 minutes / hour. A type glass filter was used. The color difference ΔE was measured for the test piece before and after the test using a spectrophotometer SE-2000 manufactured by Nippon Denshoku Kogyo Co., Ltd. The smaller ΔE indicates the smaller discoloration.

[0129] 8. Moisture and heat resistance test A 2 mm portion of a three-stage plate made by injection molding from the resin composition pellets was cut into a size of 50 mm x 45 mm, and this molded plate was left to stand for 500 hours under conditions of 85°C and 85% RH in a small environmental tester SH-241 manufactured by Espec Corp. The specific viscosity of the treated sample was measured using the method described in 2., and the Δη SP was calculated. In this evaluation, Δη SP The smaller the value, the smaller the change in molecular weight when used for a long period of time in a high-temperature, humid heat environment, and the more excellent the humid heat resistance.

[0130] 9. Notched Charpy impact strength The resin composition pellets were dried at 80 to 110°C for 12 hours, and then subjected to bending test using a JSWJ-75EIII manufactured by Japan Steel Works, Ltd. at a cylinder temperature of 230°C and a mold temperature of 90°C. The notched Charpy impact test was performed according to ISO179.

[0131] [Polycarbonate resin] PC1 (Example): Structural units derived from isosorbide (hereinafter referred to as ISS) / structural units derived from 2,2,4,4-tetramethyl-1,3-cyclobutanediol (hereinafter referred to as TMCBD: cis ratio 50 mol%) = 50 / 50 (mol%), specific viscosity 0.376 PC2 (Example): Structural units derived from ISS / structural units derived from TMCBD=70 / 30 (mol%), specific viscosity 0.369 PC3 (Example): Structural units derived from ISS / structural units derived from TMCBD=85 / 15 (mol%), specific viscosity 0.329 PC4 (Example): Structural units derived from TMCBD / structural units derived from 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane (hereinafter referred to as BP-TMC) = 85 / 15 (mol%), specific viscosity 0.391 PC5 (Example): Structural units derived from ISS / 2,2,4,4-tetraethyl-1,3-cyclobutanediol (hereinafter referred to as TECBD: cis ratio 95 mol%) = 70 / 30 (mol%), specific viscosity 0.321 PC6 (comparison example): Structural units derived from ISS / structural units derived from TMCBD=97 / 3 (mol%), specific viscosity 0.299, PC7 (comparison example): Teijin Limited Panlite L-1225 (polycarbonate resin made of structural units derived from bisphenol A) PC8 (comparison example): Structural units derived from ISS / structural units derived from 3,9-bis(2-hydroxy-1,1-dimethylethyl)-2,4,8,10-tetraoxaspiro(5,5)undecane (hereinafter SPG) = 70 / 30 (mol%), specific viscosity 0.378 PC9 (comparison example): Structural units derived from ISS / structural units derived from 1,6-hexanediol (hereinafter referred to as HD) = 75 / 25 (mol%), specific viscosity 0.371 PC10 (comparison example): Structural units derived from ISS / structural units derived from cyclohexanedimethanol (hereinafter referred to as CHDM) = 50 / 50 (mol%), specific viscosity 0.367

[0132] [Acrylic resin] PMMA Mitsubishi Chemical Corporation's ACRYPET VH-001 (structural units derived from methyl methacrylate / structural units derived from methyl acrylate=95 / 5 mol%)

[0133] [Example 1] <Production of polycarbonate resin> 253 parts of ISS, 250 parts of TMCBD, 750 parts of diphenyl carbonate (hereinafter abbreviated as DPC), and 2.4 x 10 tetramethylammonium hydroxide as a catalyst. -2 Parts and Barium Stearate 6×10 -4 The part was heated to 200°C in a nitrogen atmosphere and melted. After that, the temperature was increased to 220°C over 30 minutes and the vacuum was adjusted to 20.0 kPa. After that, the temperature was increased to 240°C over another 30 minutes and the vacuum was adjusted to 10 kPa. After that, the part was heated to 200°C in a nitrogen atmosphere and melted. After maintaining the temperature, the degree of vacuum was reduced to 133 Pa or less over 1 hour. After the reaction was completed, the mixture was discharged from the bottom of the reaction tank under nitrogen pressure, and while cooling in a water tank, it was cut with a pelletizer to obtain pellets (PC1).

[0134] <Production of Resin Composition> Polycarbonate resin PC1 and acrylic resin PMMA were used, and each resin was dried at 90°C for 6 hours or more, and then mixed so that the weight ratio was 50:50. Then, the mixture was melt-kneaded at 240°C in both the cylinder and the die using a vented twin-screw extruder [KZW15-25MG manufactured by Technobel Co., Ltd.] to obtain resin composition pellets of acrylic resin and polycarbonate resin. A part of the obtained pellets was dried at 90°C for 6 hours or more, and then test pieces for various evaluations were molded using an injection molding machine. The evaluation results are shown in Table 1.

[0135] [Example 2] <Production of Resin Composition> Except for the fact that the blend weight ratio was PC1:PMMA=10 / 90, the same operations and evaluations were carried out as in Example 1. The results are shown in Table 1.

[0136] [Example 3] <Production of Resin Composition> Except for the fact that the blend weight ratio was PC1:PMMA=90 / 10, the same operations and evaluations were carried out as in Example 1. The results are shown in Table 1.

[0137] [Example 4] <Production of polycarbonate resin> The same procedure as in Example 1 was carried out except that 354 parts of ISS, 150 parts of TMCBD, and 750 parts of DPC were used as raw materials, to obtain pellets (PC2). <Production of Resin Composition> Except for using PC2 as the polycarbonate resin, the same operations and evaluations were carried out as in Example 1. The results are shown in Table 1.

[0138] [Example 5] <Production of polycarbonate resin> The same procedure as in Example 1 was carried out except that 430 parts of ISS, 75 parts of TMCBD, and 750 parts of DPC were used as raw materials, to obtain pellets (PC3). <Production of Resin Composition> Except for using PC3 as the polycarbonate resin, the same operations and evaluations were carried out as in Example 1. The results are shown in Table 1.

[0139] [Example 6] <Production of polycarbonate resin> The same procedure as in Example 1 was carried out except that 424 parts of TMCBD, 161 parts of BP-TMC, and 750 parts of DPC were used as raw materials, to obtain pellets (PC4). <Production of Resin Composition> Except for using PC4 as the polycarbonate resin, the same operations and evaluations were carried out as in Example 1. The results are shown in Table 1.

[0140] [Example 7] <Production of polycarbonate resin> The same procedure as in Example 1 was carried out except that 354 parts of ISS, 208 parts of TECBD, and 750 parts of DPC were used as raw materials, to obtain pellets (PC5). <Production of Resin Composition> Except for using PC5 as the polycarbonate resin, the same operations and evaluations were carried out as in Example 1. The results are shown in Table 1.

[0141] [Comparative Example 1] <Production of polycarbonate resin> The same procedure as in Example 1 was carried out except that 491 parts of ISS, 15 parts of TMCBD, and 750 parts of DPC were used as raw materials, to obtain pellets (PC6). <Production of Resin Composition> Except for using PC6 as the polycarbonate resin, the same operation as in Example 1 was carried out for extrusion, but whitened pellets were obtained. The molded product after molding was also whitened and could not maintain transparency.

[0142] [Comparative Example 2] Pellets were obtained by extrusion in the same manner as in Example 1, except that only Panlite L-1225 (PC7) manufactured by Teijin Limited was used and the extrusion temperature and molding temperature were set to 280° C. The pellets were used for evaluation in the same manner as in Example 1. The surface hardness, photoelastic coefficient, and weather resistance were inferior to those of the Examples.

[0143] [Comparative Example 3] <Production of polycarbonate resin> 354 parts of ISS, 316 parts of SPG, 750 parts of DPC, and 0.8 x 10 tetramethylammonium hydroxide as a catalyst -2 parts and barium stearate 0.6 x 10 -4The mixture was heated to 200°C in a nitrogen atmosphere and melted. The temperature was then raised to 220°C over 30 minutes, and the vacuum was adjusted to 20.0 kPa. The temperature was then raised to 250°C over a further 30 minutes, and the vacuum was adjusted to 10 kPa. After maintaining this temperature for 10 minutes, the vacuum was reduced to 133 Pa or less over 1 hour. After the reaction was completed, the mixture was discharged from the bottom of the reaction tank under nitrogen pressure, and while cooling in a water tank, it was cut with a pelletizer to obtain pellets (PC8).

[0144] <Production of Resin Composition> Polycarbonate resin PC8 and acrylic resin PMMA were used, and each resin was dried at 90°C for 6 hours or more, and then mixed so that the weight ratio was 50:50. The mixture was then melt-kneaded at 250°C in both the cylinder and the die using a vented twin-screw extruder [KZW15-25MG manufactured by Technobel Co., Ltd.] to obtain resin composition pellets of acrylic resin and polycarbonate resin. A part of the obtained pellets was dried at 90°C for 6 hours or more, and then a test piece for various evaluations was molded using an injection molding machine. The evaluation results are shown in Table 1. In the moist heat resistance test, the solution viscosity was significantly reduced, and deterioration occurred.

[0145] [Comparative Example 4] Pellets were obtained by extrusion in the same manner as in Example 1, except that only Mitsubishi Rayon's ACRYPET VH-001 (PMMA1) was used and the extrusion temperature and molding temperature were set to 250° C. The pellets were used for evaluation in the same manner as in Example 1. Impact resistance was inferior to that of the Examples.

[0146] [Comparative Example 5] <Production of polycarbonate resin> The same procedure as in Example 1 was carried out except that 380 parts of ISS, 102 parts of HD, and 750 parts of DPC were used as raw materials, to obtain pellets (PC9). <Production of Resin Composition> The same procedure as in Example 1 was followed for extrusion, except that PC9 was used as the polycarbonate resin, and white pellets were obtained. The molded product after molding was also white, and did not maintain transparency. I couldn't hold it.

[0147] [Comparative Example 6] <Production of polycarbonate resin> The same procedure as in Example 1 was carried out except that 256 parts of ISS, 252 parts of CHDM, and 750 parts of DPC were used as raw materials, to obtain pellets (PC10). <Production of Resin Composition> Except for using PC10 as the polycarbonate resin, the same operation as in Example 1 was carried out for extrusion, but whitened pellets were obtained. The molded product after molding was also whitened and could not maintain its transparency.

[0148] [Table 1] [Industrial Applicability]

[0149] The resin composition of the present invention is useful as a material for optical lenses, optical disks, optical films, plastic cell substrates, optical cards, liquid crystal panels, headlamp lenses, light guide plates, diffusion plates, protective films, OPC binders, front panels, housings, trays, aquariums, lighting covers, signs, plastic windows, and the like.

Claims

1. A resin composition comprising a polycarbonate resin (A) and an acrylic resin (B) each containing 5 mol % or more and 90 mol % or less of a repeating unit (a) represented by the following formula (a-1) in all repeating units, and a weight ratio of the polycarbonate resin (A) to the acrylic resin (B) is 1:99 to 99:

1. 【Chemistry 1】 (R 1 , R 2 , R 3 , and R 4 are each an alkyl group which may be the same or different, the total number of carbon atoms of R 1 to R 4 is 4 to 40, and R 1 and R 2 , and R 3 and R 4 may be bonded to form a carbon ring.)

2. R 1 , R 2 , R 3 , R 4 The resin composition according to claim 1, wherein each of the groups is a methyl group or an ethyl group.

3. 3. The resin composition according to claim 1, wherein the acrylic resin (B) contains 10 to 100 mol % of a repeating unit (b) represented by the following formula (b) based on all repeating units: 【Chemistry 2】 (In the formula, R 5 represents a hydrogen atom or a methyl group, R 6 represents a branched or linear alkyl group having 1 to 20 carbon atoms or a cycloalkyl group having 6 to 20 carbon atoms which may have a substituent.

4. 4. The resin composition according to claim 3, wherein the repeating unit (b) is a repeating unit (b) derived from methyl methacrylate and / or methyl acrylate.

5. The resin composition according to any one of claims 1 to 4, which has a glass transition temperature of 90°C to 150°C.

6. The resin composition according to any one of claims 1 to 5, wherein a haze of a test piece having a thickness of 2 mm is 20% or less.

7. The resin composition according to any one of claims 1 to 6, which has a surface hardness of F or more.

8. Photoelastic coefficient is 60 x 10 -12 P -1 The resin composition according to any one of claims 1 to 7, wherein:

9. Notched Charpy impact strength measured according to ISO 179 is 1.5 KJ / m 2 The resin composition according to any one of claims 1 to 8.

10. A molded article obtained by molding the resin composition according to any one of claims 1 to 9.

11. A film or sheet formed from the resin composition according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Composition of polycarbonate containing fluorinated bisphenol a and polymethyl methacrylate

    JP1995003104A

  • Transparent resin film

    JP2014001267A

  • Polycarbonate resin and optical film

    JP2015137355A

  • Resin composition

    JP2015232091A

  • Thermoplastic resin composition and molded article thereof

    JP2017145318A